43 Decision making about prognoses in multidisciplinary teams: an ethnographic study. Issue 3 (1st September 2018) - Fordham, Florence Todd; McCullagh, Angela; Stone, Paddy
Abstract : Introduction: This study uses ethnographic methods to explore multidisciplinary team decision-making with a focus on prognoses at the end of life. Previous research highlights that patients carers and clinicians value accurate prognostication. Both the recognition of dying and communicating this to patients and carers were acknowledged as key unanswered research questions in the PeolcPSP. Providing quality palliative care requires different specialisms to meet the needs of the whole person – medically but also spiritually emotionally and socially. Multidisciplinary teams are considered vital to ensure that care is of the highest quality and that decisions made are evidence-based. Aim: This study aims to understand how palliative multidisciplinary teams form collective judgements about prognoses. Methods: Ethnography provided an appropriate methodology for this study as it facilitates the documentation of prognostic estimates in MDTs capturing insights into the perspectives and practices of team members exploring the influences of the structure location and nature of the meetings. Through observations and semi-structured interviews ethnography allowed an interrogation of the issues in decision-making. Results and next steps: Preliminary findings have highlighted that different disciplines use prognoses in diverse ways. For example social workers and discharge administrators use prognoses to fast-track care decisions and funding favouring an accurate numerical score whilst the medical team use prognoses as a suggestion of appropriate care preferring fluid descriptive terms. The findings will be used to will inform recommendations for future guidelines to MDTs to improve communication and decision making while discussing the prognoses of patients at the end of life. References: . Adams E, Boulton M, Watson E. The information needs of partners and family members of cancer patients: A systematic literature review. Patient Education & Counseling 2009;77(2):179–86. . Steinhauser KE, Christakis NA, Clipp EC, et al . Preparing for the end of life: Preferences of patients families physicians and other care providers. Journal of Pain & Symptom Management 2001;22(3):727–37. . Kutner JS, Steiner JF, Corbett KK, et al. Information needs in terminal illness. Social Science & Medicine1999;48(10):1341–52. . Steinhauser KE., Christakis NA, Clipp EC, et al. Factors considered important at the end of life by patients family physicians and other care providers. JAMA2000;284(19):2476–82. . The Palliative and end of life care Priority Setting Partnership (PeolcPSP). Final Report (January 2015). https://palliativecarepsp.files.wordpress.com/2015/01/peolcpsp_final_report.pdf . Blazeby J, Wilson L, Metcalfe C, et al. Analysis of clinical decision making in multi-disciplinary cancer teams. Annals of Oncology2006;17:457–60.